PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KOMITMEN KERJA GURU DI SMP NEGERI KECAMATAN SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - Thaibah Thaibah; Bustari Muchtar; Susi Evanita (Program Studi Magister Manajemen, 2013)
This study aims to identify and analyze: 1) the effect of principal leadership on teacher motivation River Junior High School district Lemons, 2) Effect of principal leadership on teachers’ commitmen Lemons River Junior High School district, 3) Effect of motivation on teachers’ commitmen Lemons River Junior High School district. Population in this study were all school teachers Secondary Schools in District Lemons River totaling 101 teachers. Mechanical Sampling using ”proportional stratified random sampling. The number of sample is 75 teachers. The date analysis technique used path analysis. The result of the study found that : 1) Leadership headmaster significant effect on teacher motivation Secondary Schools in the district of Padang Pariaman district Lemons River 2) Leadership headmaster significant effect on teachers’ work commitment Secondary Schools in the district of Padang pariaman district Lemons River. 3) Motivation significant effect on teachers’ work commitment Secondary Schools in the district of Padang Pariaman district Limai River. Keywords: principal leadership on teacher, Effect of principal leadership, Effect of motivation.